A novel method for removing heavy metals from composting system: The combination of functional bacteria and adsorbent materials. (December 2019) - Yang, Kangjie; Zhu, Longji; Zhao, Yue; Wei, Zimin; Chen, Xiaomeng; Yao, Changhao; Meng, Qingqing; Zhao, Ran
Graphical abstract: Highlights: A novel method to remove heavy metals from composting system. Sponge and cotton have good ability to remove heavy metals. Significant movement of heavy metals from outside to adsorbent column was observed. Functional bacteria have a direct and indirect affect to the heavy metals removal. Abstract: The aim of this study was to remove heavy metals from composting system using a novel method combined functional bacteria with adsorbent materials. Four types of adsorbent materials were selected in this study. Results showed that Cr had significant removal efficiency, especially in sponge treatment (19.09%) and cotton treatment (26.36%). In addition, a significant movement of heavy metals from the outside to adsorbent column was also observed. RDA results indicated that bands 1, 2, 10, 18, 19 and 20 had negative correlations with six types of heavy metals, which contributed to the removal of heavy metals. Structural equation models further confirmed functional bacteria can directly affect the removal of Cu, Cd and Cr. In addition, it can also indirectly remove Pb and Cr by changing native bacteria. In summary, this study suggested the combination of functional bacteria and adsorbent materials was effective to remove heavy metals from composting system.